Aspects of urbanization in China : Shanghai, Hong Kong, Guangzhou - Byrne Bracken, G. (Gregory) (IIAS publications series. Edited volumes, 2012)
"China's rise is one of the transformative events of our time. Aspects of Urbanization in China: Shanghai, Hong Kong, Guangzhou examines some of the aspects of China's massive wave of urbanization - the largest the world has ever seen. The various papers in the book, written by academics from different disciplines, represent ongoing research and exploration and give a useful snapshot in a rapidly developing discourse. Their point of departure is the city - Shanghai, Hong Kong and Guangzhou - where the downside of China's miraculous economic growth is most painfully apparent. And it is concern for the citizens of these cities that unifies the papers in a book whose authors seek to understand what life is like for the people who call them home"--Publisher's description.